Relationships between quality management, innovation and performance: A literature systematic review - Maríano García-Fernández; Enrique Claver Cortés; Juan José Tarí (European Research on Management and Business Economics (ERMBE), 2022)
The aim of this paper is to carry out a systematic literature review about the relationships between quality management, innovation, and performance. For that end, a search was carried out in the Web of Science and Scopus databases, and 172 articles were selected. Results show that there is a positive relationship between quality management, product and process innovation (incremental and radical), and operational and financial performance, and direct and indirect relationships. Based on these results, a set of direct and indirect relationships between these variables is proposed. The study supplements the few previous investigations on these joint relationships.
Keywords: M0; M1; M11; M15; O30; 650; Financial performance; Incremental and radical product and process innovation; Operational performance; Quality management; Systematic literature review